Panchromatic PAH-Porphyrin Hybrids with a Step-Wise Increasing π-System - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (ChemistryOpen, 2025)
The rational synthesis of three β-meso-fused porphyrins with a step-wise increasing π-system size is presented. The synthetic route, which introduces a five-membered ring between the macrocycle and an aromatic fragment, is modular in its nature and proceeds straightforwardly. The well-soluble conjugates have intriguing optical properties, namely bathochromically shifted and flattened absorption curves. Density functional theory (DFT) calculations provide insights into the electronic structure and transitions, unveiling small HOMO-LUMO gaps.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Fusion reaction; Porphyrinoids; Post-functionalization; Scholl oxidation; π-extension